Embracing uncertainty in building energy efficiency policy: A case study of a building energy standard. (April 2020) - Goulden, Shula; Erell, Evyatar; Pearlmutter, David; Garb, Yaakov
Abstract: Quantified goals for reducing energy consumption in buildings play a significant role in national and international energy policy. Calculations of potential energy savings from different interventions may be unreliable due to various types of uncertainty, resulting in a performance gap between predictions and actual energy consumption. Yet building energy policy continues to rely heavily on apparently robust calculations of energy savings, raising the question of why and how the policy process tolerates uncertainty and inaccuracy when quantification is its central logic. We describe a case study of the development of a new mandatory building energy standard, in which there is a lack of consensus on the energy it would save. We found that when this uncertainty was brought to light, the policy process raised other, unquantified logics in favour of energy efficiency measures. Using literature on calculation and expertise, we discuss how quantification is used in policy-making and how uncertainties are repressed, enabling the energy performance gap to persist. We conclude that broader awareness of the modes in which quantitative and other logics are used in energy policy, and a reframing of the types of energy savings to be made, may serve policy-making better than an illusion of calculative certainty. Highlights: Information on end-uses is central to understanding potential energy savings. Discrepancies between models and reality are inevitable but repressed. Raising uncertainty about savings introduces other logics for energy interventions. Foregrounding energy-saving uncertainties may increase success of policy measures.